A Cost Effective Green Biosorbent Simarouba glauca Seed Shell for Removal of Rhodamine B from Aqueous Solutions - Jeyagowri, B.; Yamuna, R.T. (Asian Journal of Chemistry, 2015)
This study presents the potential feasibility of a low cost green biosorbent for the removal of a basic dye rhodamine B from aqueous solutions. The biosorbent were characterized by FT-IR, SEM, XRD, BET and CHNS analysis. The effect of various parameters like initial dye concentration, contact time, pH and adsorbent dose were investigated in batch mode. The equilibrium data was analyzed using Langmuir, Freundlich, Temkin and D-R isotherm models. Equilibrium data showed best fit for Langmuir isotherm with maximum adsorption capacity 11.63 mg/g. Four kinetic models pseudo first order, pseudo second order, intraparticle diffusion and Boyd model were employed to describe the adsorption mechanism. Adsorption kinetics followed pseudo second order model with the coefficient of correlation R2 = 1. The experimental results suggested that SFTS (a biosorbent) was an excellent sorbent for removal of rhodamine B from aqueous solution.